Identification of kairomones for the biological control of Tuta absoluta (Meyrick) and Trialeurodes vaporariorum (Westwood), two major pests of tomato Solanum lycopersicum L. - Yusuf, Abdullahi Ahmed (University of Pretoria, 2021)
Thesis (PhD (Entomology))--University of Pretoria, 2021.